Technology adoption among SMEs: How is it? And what can be done to strengthen it? - Aissa Mosbah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Businesses have benefited tremendously from technological advancements, particularly in production, outsourcing, logistics, and marketing. Although large firms and Multinational Companies (MNCs) are in a better position concerning the use and adoption of technologies, small and medium-sized enterprises (SMEs) have both the agility and potential to leverage their resources, market conditions, globalization’s opportunities, and networks to improve the way they use technology and ultimately enhance their competitiveness. As seen in the literature, most research that has addressed the topic of technology adoption among SMEs has emphasized specific issues such as digitalization, information technology, cloud computing, cybersecurity, and Industry 4.0. This paper has gone beyond such a limited view to touch upon different technological aspects that are important to the functioning and/or survival of SMEs and the conditions surrounding the implementation and use of technologies. Specifically, this study examines the realities of SMEs’ technology adoption and draws lessons for policymakers in developing countries.